Javascript & Jquery interactive front-end web development - Duckett, Jon; Moore, Jack; Ruppert, Gilles Ruppert (New York John Wiley and Sons, 2014)
This book will teach you how to make youir websites more interactive, engaging, and usable. it does this by combining programming theory with examples that demonstrate how JavaScript and jQuery are used on popular sites. In no time at all you wil be able to think and code like a programmer
this book is a nic way to learn JavaScript and jQuery. Are you new to JavaScript, or have you added scripts to your web page but want a better idea of how they work , Then this book is for you. We'll not only show you how to read and write javaScript, But we'll also teach you the basics of computer programming in a simple. visual way all you need is an understanding of HTML and CSS
Content : The ABC of programming -- Basic JavaScript Instruction -- Functions, Methods & Loops -- Document Object Model -- Ebents -- jQuery -- Ajax & json -- APLs -- Error Hndiling & Debugging -- Content Panels -- Filtering, Search ing & Sorting -- Form Enancement & Balidation
"Learn how to read and write JavaScript make your sites more interactive use jQuery to simplify yoiur code recreate popular web techniques"
"Online support code sam;les and practical exercises available online at www.javascriptbook.com plus bonus reference materials"
"Techniques include slideshows and lightboxes improved forms and validation using Ajax, APIs, and JSON filtering, searching, and sorting"
12
NEW_ZAG_GN
Keywords: Programming Languages; Web developing